Omega network hash construction - Chuah, Chai Wen (2009)
Cryptographic hash functions are very common and important cryptographic primitives. They are commonly used for data integrity checking and data authentication. Their architecture is based on the Merkle-Damgard construction, which takes in a variablelength input and produces a fixed-length hash value. The basic Merkle-Damgard construction runs over the input sequentially, which can lead to problems when the input size is large since the computation time increases linearly. Therefore, an alternative architecture which can reduce the computation time is needed, especially in today's world where multi-core processors and multithreaded programming are common. An Omega Network Hash Construction that can run parallel on multi-core machine has been proposed as alternative hash function's construction. The Omega Network Hash Construction performs better than the Merkle-Damgard construction, and its permutation architecture shows that its security level in term of producing randomness digest value is better than Merkle-Damgard construction.